TRAINING COURSES AND PROFESSIONAL INTEGRATION OF DOCTORS IN EDUCATION: PATHS AND DESTINATION OF GRADUATES - Altair Alberto Fávero; Gionara Tauchen; Catia Viero Piccolo Devechi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This study aimed to investigate the trajectories and institutional destinations of graduates of doctoral programs in Education from Brazilian public universities in the last twelve years (2000-2012). The research is characterized as Mixed Methods (CRESWELL and CLARK, 2013) and was developed from data available in the electronic site of the CAPES, referring to graduate programs and Lattes Platform. Of the 3,598 graduates surveyed, a small number represents researchers who went straight to masters and doctorate degrees shortly after undergraduate studies. Almost one-third of respondents obtained doctorate degrees in between 10 and 15 years after graduation. About 15% held a doctorate between 20 and 25 years after graduation. We found that less than 25% of respondents were master's degree students in 2013 and less than 10% have contributed to the training of young doctors. We believe that the development of this research, unprecedented on this scale in the area of education, can contribute to the evaluation of expansion conditions and qualification programs and courses. In addition to taking a look at the activities and the working arrangements of the young doctors in Education in Brazil and prepare analytical frameworks that can contribute to the proposition of strategic funding policies and the setting of teachers in disadvantaged regions. Keywords: Postgraduate studies. Education. Graduate student training. Employability.